Approximated estimates for greenhouse gas emissions, 2023 ... - European Environment Agency (European Environment Agency, 2024)
The Governance Regulation ((EU) 2018/1999) requires Member States to annually report approximated greenhouse gas inventories by 31 July. A Union approximated greenhouse gas inventory is annually compiled on the basis of the Member States’ approximated greenhouse gas inventories or, if a Member State has not communicated its approximated inventories by that date, on the basis of own estimates. ...